Evaluation of Antimicrobial and Antioxidant Properties of Stem Extracts of Tinospora Cordifolia (Amrutha balli) (International Journal of Food and Nutritional Sciences, 2022)
Plants produce a diverse range of bioactive molecules, making them a rich source of different types of medicines and healing properties. Tinospora cordifolia, a well-known ayurvedic herb commonly known as giloy, has demonstrated multifaceted benefits, such as antiinflammatory, analgesic, antibacterial and antioxidant properties in animal, as well as in-vitrostudies. Hence, in the present study was aimed to evaluate the antioxidant and antimicrobial properties of methanolic stem extracts of T. cordifolia. Stem parts of T. cordifolia wassubjected to successive solvent extraction by continuous hot extraction (Soxhlet) with methanol. Antioxidant assays were carried out by in vitro model using DPPH free radicalscavenging activity. In-vitro antibacterial activity of methanolic stem extracts of T. cordifoliawas assessed using agar well diffusion method with Chloramphenicol as positive control and Dimethyl sulfoxide (DMSO) as negative control, the zones of inhibition after 48 hours of was measured in millimeters (mm). The antimicrobial activity of methanolic extract of stem of T. cordifolia were also evaluated against some pathogenic microorganisms viz. P. aeruginosa, S. aureus, K. pneumonia, and methicillin resistant Staphylococcus aureus(MRSA). Results revealed that methanolic stem extract of T. cordifolia showed the presence of phytoactives like phenols, tannins, flavonoids, saponins, terpenoids, alkaloids, proteins, and carbohydrates; while glycosides were absent in the methanolic extract of T. Cordifoliastem. Stem extracts of T. cordifolia possess potential antibacterial activity against P. aeruginosa, S. aureus, K. pneumonia, and MRSA. In conclusion, this preliminary study supplies as evidence-based study for methanolic stem extracts of T. cordifolia could be used alternative to synthetic antioxidants and antimicrobials. However, it needs to be confirmed further with in vivo studies.